Prophecy and the prophetic as aspects of Paul's theology - Hogeterp, Albert L. A. (Stellenbosch theological journal, 2018)
As the earliest documents of Christianity, Paul's Letters include extensive evidence on prophecy and the prophetic, most particularly in 1 Corinthians 12-14. In view of the influential hypothesis on "the cessation of prophecy" in Ancient Judaism on the one hand and early Jewish and Christian versatility on prophecy on the other, this essay addresses the question what prophecy meant in Paul's days and how it may be situated as a spiritual gift in Paul's theology. It reconsiders the cessation hypothesis vis-à-vis Early Judaism, providing caveats on its application to the Dead Sea Scrolls and Flavius Josephus, thereby redressing the Second Temple Jewish context of Christian origins in this respect. The essay provides a contextual reading of key passages (1 Cor 12:4-11, 13:8-13, 14:1-5, 14:20-33a), offering new insights about communal parameters of prophecy by comparing Paul's ideas with contexts of Judaism, Jewish Hellenism and the Corinthians' Greek environment.